Influence of Mydriatics on Choroidal Thickness Measurement Using Enhanced Depth Imaging-OCT - Kim, Min; Kwon, Hee Jung; Lee, Sung Chul (Optometry and vision science, 2012)
To evaluate the potential influence of mydriatics on choroidal thickness measurement using enhanced depth imaging optical coherence tomography (EDI-OCT). This was a randomized, double-blind, paired-eye study. Fifty-eight healthy eyes of 29 patients were included in this study, and one eye of each subject was designated randomly as experimental and the contralateral eye as control. A single drop of Mydrin-P (tropicamide and phenylephrine; Santen Pharmaceuticals, Japan) or a single drop of unpreserved saline was administered in the respective eyes of patients three times at 5-min intervals. Choroidal thickness (CT) was measured using EDI-OCT, and changes in CT before and after the administration of the eye drops were analyzed at the subfovea and at 0.5 mm intervals (to 3.0 mm) from the fovea at nasal, temporal, superior, and inferior locations. Linear mixed-model analysis showed no significant changes in subfoveal CT after the administration of eye drops in either the mydriatics [from 313.00 ± 90.05 μm (before) to 316.34 ± 96.91 μm (after), p = 0.500] or placebo group [from 311.07 ± 96.26 μm (before) to 313.14 ± 95.46 μm (after), p = 0.248]. CT did not significantly differ within either group at other measured locations, as we moved further from the subfoveal starting point (all p > 0.05, linear mixed model). In evaluating a possible effect of mydriatics, we detected no significant difference in CT changes between the mydriatic test group and the saline placebo group at all intervals from the fovea (all p > 0.05, linear mixed model). This study demonstrates that mydriatics (Mydrin-P) have no significant influence on clinical measurement of CT, as evaluated by EDI-OCT.